Cost-effectiveness analysis of enzyme replacement therapy for the treatment of Chinese patients with fabry disease: a Markov model - Huang, Yueyang; Yuan, Hongmei; Huang, Zhe (Frontiers in Pharmacology, 2025)
BackgroundFabry disease (FD) is an X-chromosome-linked genetic disorder. Currently, the main treatments for FD include disease-nonspecific and disease-specific treatments. Nonspecific treatment involves symptomatic management of organ involvement. On the other hand, disease-specific treatment is to regulate the activity of the corresponding enzymes, which is targeted. Among them, enzyme replacement therapy (ERT) is a classical therapy. Several studies have demonstrated the significant ameliorative effect of agalactosidase-α (ALTA-a) on cardiac and renal function in patients with FD. Despite the excellent clinical performance, there are limited pharmacoeconomic studies on ERT for FD worldwide.ObjectiveThe aim of this study was to analyze the cost-effectiveness of ERT for FD in China from the perspective of the healthcare system.MethodsWe constructed a five-state Markov model based on the disease characteristics of FD. The modeling period was 1 month. The time horizon was 3 years. The willingness-to-pay threshold was chosen as 1-3 times the gross national product (GDP) per capita. The incremental cost-effectiveness ratio (ICER) was calculated from the base case analysis, and one-way sensitivity analysis and probabilistic sensitivity analysis were performed.ResultsThe ICER value is ¥148071.95/QALY, which is between 1-3 times GDP per capita. The sensitivity analysis showed that the cost of ALTA-a had a significant effect on ICER and proved the stability of the results.ConclusionERT therapy is a cost-effective program compared to “No ERT” therapy.